2020
DOI: 10.1029/2019je006246
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Radiation Environment of Mars and Its Implication for Shielding Protection of Future Habitats

Abstract: In order to quantify the optimal radiation shielding depth on Mars in preparation for future human habitats on the red planet, it is important to understand the Martian radiation environment and its dependence on the planetary atmospheric and geological properties. With this motivation we calculate the absorbed dose and equivalent dose rates induced by galactic cosmic ray particles at varying heights above and below the Martian surface considering various subsurface compositions (ranging from dry rock to water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 32 publications
6
55
3
Order By: Relevance
“…To this purpose, we have exposed dry colonies of the cryptoendolithic black fungus C. antarcticus to increasing doses of accelerated He ions (up to 1 kGy), while mixed with Antarctic sandstones and two Martian regolith analogues. Indeed, accelerated He ions, together with protons, contribute to the major part of the absorbed dose induced by GCR in the surface and the shallow subsurface environments of Mars [40,41]. A study of the effect of elevated radiation doses, which significantly exceed the radiation on the surface of Mars (i.e., 76 mGy/yr) [5] as in the case of this experiment, is necessary for the extrapolation of biological effects on the geological time scale.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…To this purpose, we have exposed dry colonies of the cryptoendolithic black fungus C. antarcticus to increasing doses of accelerated He ions (up to 1 kGy), while mixed with Antarctic sandstones and two Martian regolith analogues. Indeed, accelerated He ions, together with protons, contribute to the major part of the absorbed dose induced by GCR in the surface and the shallow subsurface environments of Mars [40,41]. A study of the effect of elevated radiation doses, which significantly exceed the radiation on the surface of Mars (i.e., 76 mGy/yr) [5] as in the case of this experiment, is necessary for the extrapolation of biological effects on the geological time scale.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, the shielding by the regolith against GCR may play a critical role in fostering the persistence of hypothetical forms of life in the subsurface environment of Mars. However, a decrease in the absorbed dose due to GCR particles is only observed from a few centimeters beneath the surface, without significant variations within the near-surface layer [40]. Therefore, this phenomenon makes GCR particles a critical hazard not only for any putative form of life colonizing the first few centimeters of Martian regolith, but also for the future space missions around the lunar orbit and towards Martian cruise.…”
Section: Discussionmentioning
confidence: 99%
“…Röstel et al. (2020) found that, on the surface of Mars, the heavy ion primary particles contribute 9% of absorbed dose rate in a thin silicon slab phantom, while this ratio is slightly lower in a water sphere phantom, ∼8%. The heavy ion contribution to equivalent dose (not investigated here) was reported to be slightly larger, 11.5%.…”
Section: Resultsmentioning
confidence: 99%
“…However, the ED is a considerable portion of the limit for young women. Considering that most of the exposure is during the trip to and back from Mars, additional shielding is obviously necessary to maintain dose levels at the Martian surface as low as possible (Röstel et al., 2020).…”
Section: Scenarios For Short and Long Human Stays In Arabia Terramentioning
confidence: 99%
See 1 more Smart Citation